Romeo and Juliet - Shakespeare, William, 1564-1616; Raffel, Burton; Bloom, Harold (New Haven : Yale University Press, 2004)
Shakespeare's 'Romeo and Juliet' is perhaps the most read and beloved of all stage works. This annotated version of the play makes it completely accessible to readers in the 21st century. Shakespeare's Romeo and Juliet is perhaps the most read and beloved of all stage works. Now the most extensively annotated version of the play to date makes it completely accessible to readers in the twenty-first century. The new edition is a rich resource for students, teachers, and the general reader. Eminent linguist and translator Burton Raffel offers generous help with vocabulary and usage of Elizabethan English, pronunciation, prosody, and alternative readings of phrases and lines. His on-page annotations provide readers with the tools they need to comprehend the play and begin to explore its many possible interpretations. This version of Romeo and Juliet is unparalleled for its thoroughness and adherence to sound linguistic principles. In his introduction, Raffel provides historical and social contexts that increase the reader's understanding of the play. And in a concluding essay, Harold Bloom argues that Romeo and Juliet is unmatched in the world's literature "as a vision of an uncompromising love that perishes of its own idealism and intensity."
About this book -- Introduction -- Romeo and Juliet -- An essay / by Harold Bloom -- Further reading -- Finding list.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Romeo -- (Fictitious character) -- Drama; Juliet -- (Fictitious character) -- Drama; Juliet -- (Fictitious character); Romeo -- (Fictitious character); Conflict of generations -- Drama; Verona (Italy) -- Drama; Vendetta -- Drama; Youth -- Drama; LITERARY CRITICISM -- Shakespeare; DRAMA -- Shakespeare; Conflict of generations; Vendetta; Youth; Italy -- Verona; tragedies; Tragedies (Drama); Drama; Tragedies; Tragedies (Drama); Tragédies.